Skin Closure Technique and Postprocedural Pain after Spinal Cord Stimulator Implantation: A Retrospective Review - Markus A. Bendel; Ryan S. D’Souza; Taylor J. North; Thomas P. Pittelkow; Jonathan M. Hagedorn (Pain Research and Management)
Spinal cord and dorsal root ganglion stimulation are minimally invasive surgical techniques used to treat an array of chronic pain disorders. There is a paucity of data related to defining best practices in these specific patient populations, and historically, providers have relied on consensus committees to opine on the best techniques for patient safety and experience. The most efficacious mechanism of surgical closure—specifically a running suture closure compared to a surgical staple closure—is debated. A retrospective review of 155 patients implanted with either a spinal cord or dorsal root ganglion stimulator between 2017 and 2019 was undertaken to determine if the type of surgical closure was related to degree of postoperative surgical site discomfort. The primary outcome showed no statistically significant difference on postoperative pain scores between the suture (6.0 (IQR 5.0–8.0)) and staple (7.0 (IQR 5.0–8.0)) cohorts at postoperative day (POD) #1 (adjusted β 0.17 (95% CI −0.61 to 0.95), P=0.670). This finding held for postoperative pain scores at POD #10 as well (staples (1.0 (IQR 0.0–4.0)) and suture (2.0 (IQR 0.0–5.0), adjusted β −0.39 (95% CI −1.35 to 0.58), P=0.432)). A regression analysis was performed to identify secondary factors impacting postoperative pain scores. Higher preoperative pain score (β 0.50 (95% CI 0.09 to 0.92), P=0.019) and female gender (β 1.09 (95% CI 0.15 to 2.02), P=0.023) were predictive of higher incisional pain scores at POD#10. Increasing age was associated with decreased incisional pain scores at POD#10 (β −0.06 (95% CI −0.09 to −0.03), P<0.001). These findings are of interest to the pain practitioner and may be valuable in preoperative discussions with prospective patients.